An Empirical Comparison of Soviet and American Business Negotiations - Graham, John L.; Evenko, Leonid I.; Rajan, Mahesh N. (Journal of International Business Studies, 1992)
Fifty-six Soviet businesspeople and 160 American businesspeople participated in simulated intracultural, one-on-one, buyer-seller negotiations. All participants completed questionnaires after the negotiation sessions, and six negotiators from each cultural group were videotaped during the interactions. Analysis of the questionnaire data indicated that Soviet negotiators achieved higher individual profits when using a competitive approach in negotiations. This result is in contrast to a more cooperative approach associated with higher profits for the American participants. Analysis of the videotapes suggests both similarities and differences in observed bargaining behaviors across the two cultural groups.